Upaya Kepala Sekolah dalam Pemberdayaan Pegawai Tata Usaha di SMA Negeri 1 Pseksu Kabupaten Lahat - Andrianto (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2019)
This study takes the title "Efforts of School Principals in Empowering Administrative Employees in SMA Negeri 1 PSEKSU Kab. Lahat ". The problem in this thesis is how the principal's efforts in empowering administrative staff in SMA Negeri 1 PSEKSU Kab. Lahat? And what are the supporting and inhibiting factors of school principals in empowering administrative staff in SMA Negeri 1 PSEKSU Kab. Lahat ?. The purpose of this study was to determine the efforts of school principals in empowering administrative staff in SMA Negeri 1 PSEKSU in Lahat Regency and to know the supporting and inhibiting factors of school principals in empowering civil servants in the SMAN region.There is a type of data in research is a qualitative data that includes information about things that are related to the head of the school in empowerment of employees or businesses in SM Anegeri 1 PSEKSU Kab. Lahat. Sources of data in this study consisted of primary data and secondary data, primary data consisted of school principals, administrative staff and teachers, while secondary data were a number of supporting data in the form of documentation, archives and literature-literature that were subject to the research discussed. For data collection, researchers used observation techniques, interviews and documentation.Then it was concluded that the efforts of the headmaster in empowering the administrative staff obtained in this study were, first, the principal had empowered quite well and was connected with the vision of the school. Second, the principal conducts empowerment directed towards using examples, third, establishes good communication with administrative staff, fourth, the principal reviews the school's organizational structure so that staff can find out their positions and tasks, fifth, the principal strengthen team / group keraja by means of communicating well, holding joint meetings, involving administrative staff to attend training, sixth, the principal encourages personal development of administrative staff with, seventh, the principal makes the service a focus so that it can attract interest community to register their children and can increase the number of students in high schools 1 Pseksu Kab. Lahat, and finally the principal conducts an evaluation. The supporting factors in empowering administrative staff are: First, there is trust between superiors and subordinates Second, mutual respect and mutual understanding of the opinions expressed Third, believe that empowerment will bring benefits to the school being led. While the inhibiting factors in the empowerment are: the number of administrative staff still little, the education level of administrative staff is still low, and the lack of funding to implement empowerment.